MARKET ORIENTATION TO IMPROVE MARKETING PERFORMANCE THROUGH THE COMPETITIVE ADVANTAGES OF BATIK SMEs - Rokhman, M. Taufiq Noor (Jurnal Aplikasi Manajemen, 2019)
The purpose of this study was to investigate competitive advantage as a mediator of the effect of market orientation on the marketing performance of Batik UKM in Malang. The population of this research is 100 batik SME owners in Malang. Sampling in this study uses saturated / census sampling, meaning that all populations are used as samples so that the sample of this study amounted to 100 respondents. Data analysis uses Structural Equation Modeling (SEM). The results showed that there was a direct and positive influence of market orientation on the marketing performance of batik SMEs in Malang City and the competitive advantage was able to mediate the influence of market orientation on the marketing performance of batik SMEs in Malang City.